Does container-based sanitation align with sanitation sectoral planning in Lima? - López, Hellen; Ofori, Alesia D.; Mdee, Anna L.; Llaxacondor, Arturo (IWA Publishing, 2025)
The paper explores the potential of Container-Based Sanitation (CBS) as an off-grid sanitation option in addressing extreme sanitation inequalities in informal urban settlements in Lima, Perú. It achieves this by evaluating the conflicting and political tensions within the formal and informal structures of state public service provision in Lima using qualitative data collected through semi-structured interviews with government officials, third-sector organizations, citizens of informal urban settlements, and academia. The paper argues that although the CBS provision has high social acceptability among its users within Lima's informal settlements, the state of Lima's fragmented sanitation sector regime hinders the possibility of scaling sanitation innovations. In Lima, scaling up CBS among informal settlements remains challenging as conventional sewerage is prioritised in WASH policy discourse and implementation. Even for CBS users, the technology was seen as a stopgap solution until they finally access sewered sanitation provided by the state, mainly because of the state's inability to fully address wastewater challenges and the assumption that conventional sewerage will eventually arrive.
Keywords: 33 Built Environment and Design; 4104 Environmental Management; 40 Engineering; 41 Environmental Sciences; 4011 Environmental Engineering; 3304 Urban and Regional Planning; 6 Clean Water and Sanitation